2019
DOI: 10.3389/fpsyt.2019.00279
|View full text |Cite
|
Sign up to set email alerts
|

Attention Problems Predict Risk of Violence and Rehabilitative Engagement in Mentally Disordered Offenders

Abstract: Mentally disordered offenders (MDOs) endorse difficulties with attention, impulsivity, and hyperactivity. Assessing these difficulties among MDOs may confer practical benefits for the management and provision of care for this population, by informing strategies to improve rehabilitative engagement and risk assessments for violence. However, there is a dearth of literature exploring these cognitive problems in MDOs in relation to outcome factors. Forty-eight MDOs from a high-security hospital completed the QbTe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…This suggests that those participants had no less emotional awareness or clarity than those without self-harm and/or suicide attempt and raises the question of whether people who self-harm perceive themselves as aware and clear about their emotions at the time, but are nevertheless unable to refrain from maladaptive behaviors. Another explanation, as previously mentioned in another part of this discussion, is that the items on these scales place too high a demand on forensic psychiatric patients' abstract thinking, especially since cognitive deficits have been found to be common in such groups (e.g., Puzzo et al, 2019). This in turn raises problems in relation to the use of self-reports in forensic psychiatric settings, which are further complicated by the general low reading level in such contexts (Svensson et al, 2015).…”
Section: Dimensions and Levels Of Emotion Regulation In Relation To Self-harm In Forensic Psychiatric Patientsmentioning
confidence: 95%
See 1 more Smart Citation
“…This suggests that those participants had no less emotional awareness or clarity than those without self-harm and/or suicide attempt and raises the question of whether people who self-harm perceive themselves as aware and clear about their emotions at the time, but are nevertheless unable to refrain from maladaptive behaviors. Another explanation, as previously mentioned in another part of this discussion, is that the items on these scales place too high a demand on forensic psychiatric patients' abstract thinking, especially since cognitive deficits have been found to be common in such groups (e.g., Puzzo et al, 2019). This in turn raises problems in relation to the use of self-reports in forensic psychiatric settings, which are further complicated by the general low reading level in such contexts (Svensson et al, 2015).…”
Section: Dimensions and Levels Of Emotion Regulation In Relation To Self-harm In Forensic Psychiatric Patientsmentioning
confidence: 95%
“…For example, individuals residing in forensic settings may demonstrate difficulties in being able to reflect and think about their own feelings and emotions, which eventually may lead to emotions becoming overwhelming and expressed in disruptive behaviors (Velotti and Garofalo, 2015). Second, a major concern that arose during the data collection in the current study was whether DERS captures the full construct of emotion regulation in forensic samples, given the complex interactions of psychiatric comorbidities and cognitive deficits (Garieballa et al, 2006;Puzzo et al, 2019). The DERS has been used in prison samples (e.g., Garofalo and Velotti, 2017;Garofalo et al, 2018), but forensic psychiatric patients demonstrate even more complex needs than prison population, and this could affect the applicability of the DERS or other self-reporting instruments of emotion regulation.…”
Section: Emotion Regulation In Forensic Psychiatric Patientsmentioning
confidence: 99%
“…Cognitive defects are a core symptom of schizophrenia that affect the patient’s ability to make decisions and to manage independent living (30). Recently it was shown that attention problems in a group of forensic psychiatric patients correlated with future risk of violence and less rehabilitative engagement (31). Although there is currently no guaranteed effective treatment for cognitive symptoms, experimental treatment with transcranial magnetic stimulation has proven to be able to improve working memory in schizophrenia patients (32) and it has been suggested that pharmacotherapy for substance use could improve executive functions in misuse patients (33).…”
Section: Cognitive Functionmentioning
confidence: 99%
“…Poor brain health of the patients has been proposed as one explaining factor that may be the target for future interventions in forensic psychiatry ( 1 ). Brain health is correlated with cognitive function, an essential element for the success of forensic psychiatric rehabilitation ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%